Kepemimpinan Transformasional dan Efikasi Diri Terhadap Kinerja Karyawan - Muzakki Muzakki; Anggita Rinda Pratiwi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
The purpose of this study was to study partial and simultaneous research of transformational leadership and self-efficacy on job performance. The sample in this study were employees at PT. Panca Mitra Multiperdana. The sampling technique used was random sampling with the number of samples taken were 128 employees. Meanwhile, to collect our data using a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple linear regression analysis. The findings of this study reveal that transformational leadership and self-efficacy have a positive and significant influence on employee job performance partially. Besides, simultaneously both constructs of job performance also have a positive and significant effect.